Investigation of NNN Pincer Ruthenium(II) Complexes with a Pendant Hydroxyl Group for N‐Monomethylation of amines and Nitroarenes by Methanol. Issue 11 (5th May 2022) - Li, Kangkang; Li, Jin‐Feng; Yin, Bing; Zeng, Fanlong
Abstract: A family of air‐ and moisture‐stable NNN pincer ruthenium(II) complexes with a pendant OH were developed, which exhibit unprecedented high reactivity and selectivity in N‐monomethylation of amines and nitroarenes using methanol. The investigation reveals adopting the combination of 1H‐pyrazole‐1‐yl and 3, 5‐dimethyl‐4‐hydroxyethyl‐1H‐pyrazol‐1‐yl as the two assistant arms of the pyridyl‐backbone is a suitable choice. The mechanism study discloses that, during the catalytic cycle, dehydrogenation of methanol to form formaldehyde is a fast and reversible step. Abstract : A family of NNN pincer Ru(II) complexes with a pendant OH were developed, which exhibit unprecedented high reactivity and selectivity in N‐monomethylation of amines and nitroarenes using methanol. The study discloses the pendant OH group facilitates oxidative dehydrogenation of methanol via a synergistic pathway and, during the catalytic cycle, dehydrogenation of methanol to form formaldehyde is a fast and reversible step.